2004
DOI: 10.1038/sj.ijo.0802751
|View full text |Cite
|
Sign up to set email alerts
|

Insulin downregulates M2-muscarinic receptors in adult rat atrial cardiomyocytes: a link between obesity and cardiovascular complications

Abstract: OBJECTIVE:To determine whether decreased cardiac parasympathetic activity observed in obesity is due to insulin-induced alterations in cardiac M 2 -muscarinic receptors and/or adenylyl cyclase activity. DESIGN AND METHODS: After incubation with increasing concentrations of insulin, adult rat atrial cardiomyocytes were assayed for M 2 -muscarinic receptor binding density and affinity, and for M 2 R mRNA expression using RT-PCR analysis. Forskolinstimulated adenylyl cyclase activity and its inhibition by carbach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Likewise, radioligand binding studies show increased M 2 receptors in the vas deferens of rats after depleting insulin with STZ (28), and again this effect was reversed by exogenous insulin. M 2 receptors are the dominant muscarinic receptor in the heart and expression of M 2 receptors in cultured rat atrial myocytes was also reduced by insulin (41). Our data show that insulin reduced M 2 receptor function rapidly; we were able to decrease M 2 receptor function after only 2 hours incubation with insulin.…”
Section: Discussionsupporting
confidence: 49%
“…Likewise, radioligand binding studies show increased M 2 receptors in the vas deferens of rats after depleting insulin with STZ (28), and again this effect was reversed by exogenous insulin. M 2 receptors are the dominant muscarinic receptor in the heart and expression of M 2 receptors in cultured rat atrial myocytes was also reduced by insulin (41). Our data show that insulin reduced M 2 receptor function rapidly; we were able to decrease M 2 receptor function after only 2 hours incubation with insulin.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, when CHRM2 is knocked out in mice, the adult mice weigh approximately 5% less then wild‐type littermates (53). Finally, it has been shown that insulin downregulates M 2 ‐muscarinic receptors in rat atrial cardiomyocytes (54). In our study, we genotyped 28 SNPs within the CHRM2 gene, and rs1824024 showed significant association ( P = 0.046, β‐estimate = −0.104) to BMI in linked families.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated density of 0.88 ϫ 10 6 receptors per cell is about onehalf of the density reported for intact cardiomyocytes from rat atria. The latter value is 1.7 ϫ 10 6 receptors per cell (47), which may be an underestimate. It was determined from the binding of N- [ 3 H]methylscopolamine, which presumably labeled only those receptors that were located at the plasma membrane.…”
mentioning
confidence: 89%